2018
DOI: 10.1140/epjc/s10052-018-5519-4
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter stability and one-loop neutrino mass generation based on Peccei–Quinn symmetry

Abstract: We propose a model which is a simple extension of the KSVZ invisible axion model with an inert doublet scalar. Peccei-Quinn symmetry forbids tree-level neutrino mass generation and its remnant Z 2 symmetry guarantees dark matter stability. The neutrino masses are generated by one-loop effects as a result of the breaking of PecceiQuinn symmetry through a nonrenormalizable interaction. Although the low energy effective model coincides with an original scotogenic model which contains right-handed neutrinos with l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…There are many attempts to connect axion and neutrino mass in the literature [9][10][11][12][13][14][15][16][17].…”
Section: Scalar Fieldsmentioning
confidence: 99%
“…There are many attempts to connect axion and neutrino mass in the literature [9][10][11][12][13][14][15][16][17].…”
Section: Scalar Fieldsmentioning
confidence: 99%
“…the question why the observable QCD vacuum angle θ = θ QCD + arg det M q (with M q the quark mass matrix) is such a small quantity (current measurements of the neutron electric dipole moment imply | θ| 10 −11 [3][4][5]), its experimental detection would not only unequivocally solve the strong-CP problem, but potentially also provide an answer (or complement the answer) on the question of the nature of the cosmological dark matter, another pressing issue in contemporary physics research. At the same time a model with PQ symmetry breaking can lead to massive Majorana or Dirac neutrinos depending on the choice of assigning PQ charges to the SM particles and Higgses [6][7][8][9][10][11][12][13][14][15]. Moreover, the fact that axions and PQ symmetries arise quite naturally in superstring theory [16] increases their popularity further.…”
Section: Introductionmentioning
confidence: 99%
“…[45]: ∆u = 0.847(50), ∆d = −0.407(34), ∆s = −0.035(13),m u = 2.27(9) MeV, m d = 4.67(9) MeV, M π = 136.10(1.82) MeV, z = 0.485(19), w = 0.025(1), mN = 0.8726(31) GeV, d16 = 0.4(1.3) GeV −2 , d 18 = −0.44(24) GeV −2 , (62)…”
mentioning
confidence: 99%
“…GeV. Other studies on the link between U(1) PQ symmetry and neutrino/flavour can be found in [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: The Axion and The Dirac Neutrinomentioning
confidence: 99%